2005
DOI: 10.1111/j.1365-263x.2006.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of oral and maxillofacial pathology found in children over a 30‐year period

Abstract: Summary.Aim. The vast majority of oral diseases are confined to oral tissues, but numerous underlying systemic conditions may present with signs and symptoms within the oral cavity. Since the epidemiology of diseases is variable between regions, the authors carried out Europe's first paediatric-based survey of oral and maxillofacial pathology specimens submitted for diagnosis. Design. All entries for specimens from children between the ages of 0 and 16 years during the 30-year period from 1973 to 2002 were ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

57
203
11
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(283 citation statements)
references
References 11 publications
57
203
11
12
Order By: Relevance
“…In our study, malignancy was very low, only 4 out of 97 biopsies (4.1%) similar to the studies reportedby Jones and franklin [13] (1%) and Monique Maria MeloMouchrek [2] (8.9%). Among the fibro osseous lesions, fibrous dysplasia was the commonest with 3 cases followed by one case of cemento osseous dysplasia.…”
Section: Neoplastic Lesionssupporting
confidence: 77%
See 1 more Smart Citation
“…In our study, malignancy was very low, only 4 out of 97 biopsies (4.1%) similar to the studies reportedby Jones and franklin [13] (1%) and Monique Maria MeloMouchrek [2] (8.9%). Among the fibro osseous lesions, fibrous dysplasia was the commonest with 3 cases followed by one case of cemento osseous dysplasia.…”
Section: Neoplastic Lesionssupporting
confidence: 77%
“…Many studies showed an almost equal distribution between both genders (M:F = 1.05:1) as reported by Gultelkin [12], Das and Das [9] and Jones and Franklin [13]. But in our study, the pathologies were more common in females.…”
Section: Discussioncontrasting
confidence: 45%
“…Studies conducted in dental schools, both with patients in routine dental treatment or referred for stomatological evaluation, in spite of probably showing a different picture from the general population, may better represent a model of what occurs in daily practice of the profession 6,[11][12][13][14] . In contrast, studies with samples derived from oral surgical pathology laboratories do not evaluate the frequency of clinically diagnosed lesions, basing their results on diseases diagnosed and/or treated by surgical procedures 15,16 . Studies selecting populations by age group provide highly specific information, therefore, need to be analyzed separately.…”
Section: Discussionmentioning
confidence: 99%
“…Following inclusion criteria were considered 1. All intra-osseous cases with evidence of radiographic changes in bone were included.…”
Section: Dentistry Sectionmentioning
confidence: 99%